2012
DOI: 10.1134/s0023158412030081
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical simulation of self-oscillations in methane oxidation on nickel: An isothermal model

Abstract: The dynamics of methane oxidation on nickel was studied by mathematical modeling within the framework of an 18 step microkinetic scheme. The model examined predicts the appearance of self oscilla tions caused by the periodic oxidation-reduction of nickel in the reaction proceeding under isothermal con ditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…At elevated pressures, the self-sustained rate oscillations in catalytic oxidation reactions over transition metals are more probably to follow the redox mechanism based on the reversible bulk oxidation of the catalyst. In full agreement with this hypothesis, the mathematic modeling of the oxidation of methane over nickel confirmed that the rate oscillations can arise because of the periodic oxidation and reduction of nickel [62] and that metallic nickel in this reaction is more active than NiO.…”
Section: Discussionsupporting
confidence: 62%
“…At elevated pressures, the self-sustained rate oscillations in catalytic oxidation reactions over transition metals are more probably to follow the redox mechanism based on the reversible bulk oxidation of the catalyst. In full agreement with this hypothesis, the mathematic modeling of the oxidation of methane over nickel confirmed that the rate oscillations can arise because of the periodic oxidation and reduction of nickel [62] and that metallic nickel in this reaction is more active than NiO.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, when y CH4 is lowered to 0.47, the surface becomes saturated mainly with Ox and OH*. It corresponds to the non-reactive state in which the surface is oxidized (Lashina et al, 2012). However, this transition is continuous; therefore, it is second-order.…”
Section: Feed Concentration Of Methane (Y Ch 4 )mentioning
confidence: 99%
“…The effects of diffusion of adsorbed species, lattice coordination number and inactive impurities on the surface are also evaluated. Lashina et al (2012). According to these authors, the mechanism of CPOx can be described by an 18-step elementary reaction (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…with fast (x 2 ), intermediate (x 1 ), and slow (z) variables and small parameters µ and ε, the relaxation and mixed-mode oscillations and also chaotic dynamics were found [7,25,26]. Consider the one-parameter family of two-dimensional dynamical subsystems with the parameter ż…”
Section: Introductionmentioning
confidence: 99%